Lamastu : an edition of the canonical series of Lamastu incantations and rituals and related texts from the second and first millennia B.C. - Farber, Walter, 1947- (Eisenbrauns, 2014)
Lamastu was one of the most important Mesopotamian demons, playing a dominant role in the magico-religious and magico-medical beliefs and practices of ancient Mesopotamia for nearly two millennia. Yet, she has never been the subject of a scholarly monograph dedicated to the textual and visual evidence for her, her activities, and the measures that ancient magical specialists took to counter her. This volume also falls short of this description, because it covers only one part of the material: it is an edition of the textual record only, which is, however, collected here as completely as seems possible today. Walter Farber, who has studied these materials for decades, presents a comprehensive collection of all of the known texts, the texts of the primary incantations in a "score" format, and transliteration and translation of a number of ancillary texts. This much-awaited volume will fill the void in the literature on this aspect of the life and thought of ancient Mesopotamian peoples regarding the character of this malevolent creature and the means of warding off the threat that she posed.
Keywords: Lamashtu -- (Assyro-Babylonian deity); Lamaštu (divinite assyro-babylonienne); Mythology, Assyro-Babylonian.; Mythologie assyro-babylonienne.; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion.; Mythology, Assyro-Babylonian; Incantations akkadiennes.; Religion assyro-babylonienne.; Lamassu.